MEETING THE CHALLENGE OF INNOVATION IN THE BANKING INDUSTRY: AN ANALYSIS THROUGH DYNAMIC CAPABILITIES - MOUSSAVOU, Jean (Bankers, Markets & Investors, 2022)
The question over innovation, and more importantly over its organization and management, has become a topical issue in the banking sector. Indeed, banks are faced with changes in the operating environment that are increasingly protean and rapid, in contrast to the situation of relative stability that has prevailed over the last few decades. This stability is now being challenged by new entrants, the fintech startups, considered by some experts as the real "drivers" of innovation in the sector. By applying the different phases of the Dynamic Capabilities (DCs) model proposed by Teece (2007; 2019) (Sensing, Seizing, Transforming), this research has helped us understand how banking organizations are trying to grasp the environmental changes at work and create their own internal capabilities to innovate. On the one hand, by capturing available external knowledge (Sensing dynamic), notably through collaboration mechanisms with new entrants, and on the other hand, by relying on the banking actor's capacities to integrate them into its own resources and skills base (Seizing and Transforming dynamic). Our results show that the framework relatively constrained by the banking regulation does not allow to effectively activate the three phases : banking organizations are confronted with a certain conservatism towards innovation due to the weight of internal structures and the importance of tradition. This situation prevents a complete CDs formation process integrating all three phases of the model at the same time. In this respect, we propose to characterize innovation within banks as incremental. We see banks innovating progressively rather than radically: innovation within banks tends more towards the improvement of existing skills than towards their total destruction. Finally, we propose the addition of a fourth CD applicable to banks: the "dynamic optimization capacity", whose particularity is to fit in between the Seizing and Transforming dynamics of the model proposed by Teece.